2011
DOI: 10.1179/2045772311y.0000000019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 24-hour cardiovascular and autonomic function in paraplegia, tetraplegia, and control groups: Implications for cardiovascular risk

Abstract: Background: Fluctuations in 24-hour cardiovascular hemodynamics, specifically heart rate (HR) and blood pressure (BP), are thought to reflect autonomic nervous system (ANS) activity. Persons with spinal cord injury (SCI) represent a model of ANS dysfunction, which may affect 24-hour hemodynamics and predispose these individuals to increased cardiovascular disease risk. Objective: To determine 24-hour cardiovascular and ANS function among individuals with tetraplegia (n = 20; TETRA: C4-C8), high paraplegia (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
64
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 62 publications
7
64
0
Order By: Relevance
“…The first is that the results of previous studies that tried to establish differences between high-and low-level paraplegia did not find significant differences between levels. [13][14][15] This concurs with the results obtained from one of our secondary analyses. The other reason is because differences in HRV are not always due to altered or preserved autonomic function, but can be due to long-term use of a wheelchair and/or the lifestyle adopted.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The first is that the results of previous studies that tried to establish differences between high-and low-level paraplegia did not find significant differences between levels. [13][14][15] This concurs with the results obtained from one of our secondary analyses. The other reason is because differences in HRV are not always due to altered or preserved autonomic function, but can be due to long-term use of a wheelchair and/or the lifestyle adopted.…”
Section: Discussionsupporting
confidence: 91%
“…15 The RMSSD estimates the short-term components of the HRV and is considered an indirect measure of the vagal cardiac tone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We reported that the prevalence of hypotension recorded in the medical record was 39%, 21 and documented hypotension over the course of a typical 24-hour day in 70% of subjects with tetraplegia. 22 However, we found that the diagnosis of hypotension was less than 1% and treatment with prescription anti-hypotensive agents was negligible (3 of 1291 records: 0.2%) in veterans with tetraplegia. 21 These findings most likely reflect the limited number of FDA approved agents available to treat hypotension and OH and a paucity of data supporting the safe and effective use of these medications in the SCI population.…”
Section: Discussionmentioning
confidence: 72%